Routing TCP/IP, volume II : CCIE professional development - Doyle, Jeffrey (Indianapolis, IN : Cisco Press, 2017)
Routing TCP/IP, Volume II, Second Edition will help you thoroughly understand modern exterior routing protocols and implement them with Cisco routers. Covers routing and switching techniques that form the foundation of all Cisco CCIE tracks. Review core inter-domain routing concepts, and discover how exterior routing protocols have evolved. Master BGP's modern operational components. Effectively configure and troubleshoot BGP. Control path attributes and selection to define better routes. Take full advantage of NLRI and routing policies. Provide for load balancing and improved network scalability. Extend BGP to multiprotocol environments via MP-BGP. Deploy, configure, manage, troubleshoot, and scale IP multicast routing. Implement Protocol Independent Multicast (PIM): Dense Mode, Sparse Mode, and Bidirectional. Operate, configure, and troubleshoot NAT in IPv4-IPv4 (NAT44) and IPv6-IPv4 (NAT64) environments. Avoid policy errors and other mistakes that damage network performance.
oif 20/01/2020
Loans
Keywords: Routers (Computer networks); TCP/IP (Computer network protocol); Internetworking (Telecommunication); Computer network protocols